2007
DOI: 10.1021/jp070902n
|View full text |Cite
|
Sign up to set email alerts
|

A Linear AC Trap for Polar Molecules in Their Ground State

Abstract: A linear AC trap for polar molecules in high-field seeking states has been devised and implemented, and its characteristics have been investigated both experimentally and theoretically. The trap is loaded with slow 15 ND 3 molecules in their ground state (para-ammonia) from a Stark decelerator. The trap's geometry offers optimal access as well as improved loading. We present measurements of the dependence of the trap's performance on the switching frequency, which exhibit a characteristic structure due to nonl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 48 publications
1
34
0
3
Order By: Relevance
“…Similar trap depths were later obtained for the same molecule with a linear ac trap [12]. In the meantime, Katori and coworkers achieved trapping of about 100 ground-state Sr atoms with a lifetime of 80 ms in a microstructured ac trap on a chip [13].…”
Section: Introductionsupporting
confidence: 61%
“…Similar trap depths were later obtained for the same molecule with a linear ac trap [12]. In the meantime, Katori and coworkers achieved trapping of about 100 ground-state Sr atoms with a lifetime of 80 ms in a microstructured ac trap on a chip [13].…”
Section: Introductionsupporting
confidence: 61%
“…Slowly moving molecules produced using this technique have already found many applications, including: high-resolution spectroscopy [14,18] and lifetime measurements [72,73]; trapping in static and AC electric fields [74][75][76][77][78]; magneto-electrostatic and magnetic trapping [79]; reflection from a microstructure or permanent magnet array [80,81] and tunable-energy collision studies [82]. More recently, a molecular synchrotron [83] has been constructed which confines molecules in bunches orbiting inside a split hexapole ring -a direct analogue of the charged-particle synchrotrons used for high-energy collision experiments.…”
Section: Stark Decelerationmentioning
confidence: 99%
“…The linear AC trap designed by Schnell et al [78], shown in Fig. 9(b), consisting of four 8 mm length double rods, has been used to capture 15 ND 3 molecules which were decelerated to 15 ms −1 before trapping.…”
Section: Ac Electric Trapsmentioning
confidence: 99%
See 1 more Smart Citation
“…By alternating the focussing and defocussing directions at a suitable rate, molecules are confined near the trap centre. Such ac electric traps have already been used to trap polar molecules in strong-field-seeking states [41][42][43], and also to trap ground-state atoms [44,45], and sympathetic cooling of molecules in ac traps has been proposed [44,45].…”
Section: B Cooling In An Ac Electric Trapmentioning
confidence: 99%